2023
DOI: 10.7759/cureus.41461
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Brucellosis Among the General Population in Qassim Region, Saudi Arabia: A Cross-Sectional Study

Ayman A Harbi,
Abdulmalik S Almarshad,
Omar A Alaqeel
et al.

Abstract: Background Brucellosis is an endemic infection in the Middle East. The World Health Organization has identified the illness as one of the most prevalent "neglected zoonotic diseases." Public perceptions regarding brucellosis infection vary across different regions. Thus, this study aimed to assess the knowledge, attitudes, and practices concerning brucellosis among the general population in the Qassim region of Saudi Arabia. Methods A descriptive, cross-sectional study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Having heard of brucellosis was reported by a total of 1,913 (57.1%) participants with a range of 50–73.6% between the studies who mostly demonstrated a good knowledge (range 53.1–90%). Factors such as being a male, old, and having a high level of education were significantly associated with good knowledge ( 10–12 ). While evaluating the understanding of the general public regarding brucellosis holds significance, it is crucial to assess the knowledge and behavior of individuals working with animals.…”
Section: Introductionmentioning
confidence: 99%
“…Having heard of brucellosis was reported by a total of 1,913 (57.1%) participants with a range of 50–73.6% between the studies who mostly demonstrated a good knowledge (range 53.1–90%). Factors such as being a male, old, and having a high level of education were significantly associated with good knowledge ( 10–12 ). While evaluating the understanding of the general public regarding brucellosis holds significance, it is crucial to assess the knowledge and behavior of individuals working with animals.…”
Section: Introductionmentioning
confidence: 99%